TEACHERS' PERCEPTIONS OF SMARTPHONE-BASED SUMMATIVE ASSESSMENT IN MEASURING STUDENTS' ENGLISH LANGUAGE PROFICIENCY - Ayu surayya, Siti; Husnu, Muhammad; Marlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Although previous studies have examined smartphone-based assessment in EFL contexts, empirical research directly addressing teachers' experiences with smartphone-based summative assessment, particularly regarding its accuracy and implementation challenges remains limited. This study aims to explore teachers' perceptions of the smartphone-based summative assessment, to examine whether the results accurately reflect students' actual abilities, and to identify the challenges and benefits teachers experience in its implementation. This research employed a descriptive qualitative method, conducted at MA NW Korleko, involving two English teachers selected through purposive sampling. Data was collected through observation, semi-structured interviews, and documentation, and analyzed using an interactive model of data reduction, data display, and conclusion drawing. The findings show that smartphone-based summative assessment was effective in terms of administrative convenience and grading speed, but not yet effective in measuring students' English proficiency, as the application used could only assess two skills, reading and writing. Regarding accuracy, results did not always reflect students' true proficiency, as some students reportedly exploited a security loophole to bypass anti-cheating features. This study concludes that the effectiveness of smartphone-based summative assessment depends heavily on the quality of the application and the readiness of supporting technical infrastructure, rather than on the assessment method itself.